The Argentine Banking and Exchange Rate Crisis of 2001: Can We Learn Something New from Financial Crises? - D'Amato, Laura (2002)
After more than ten years under a Currency Board regime, successful in abating inflation and ensuring macroeconomic and financial stability, in January 2002, the country was forced to abandon the “Convertibilidad” and moved to a floating exchange regime. Is this twin crisis different from those experienced by Argentina in 1995 or earlier in the 1980’s? A remarkable difference from past experiences was the apparent strength of the Argentine Financial System, as a consequence of deliberate and systematic process of reforms that put its regulatory framework close to those of developed countries. However, the crisis revealed two sources of financial fragility ´probably underestimated during the good times. First, the combination of a currency board regime and highly dollarized banks’ balance sheets implied a solvency risk for the financial system in case the economy had to adjust to a shock either trough a nominal devaluation or a deflationary process. The other hidden risk for the financial system was the non regulated exposure of banks to sovereign risk. Using a dynamic panel data model we study the behavior of individual banks’ deposits during the prolonged twin crisis suffered by Argentina since November 2000. Our aim was to determine if this event could have been a “sun spot” phenomenon, i.e. a random event not related to the real economy or the consequence of a change in economic agents perception about the trend of the Argentine economy., i.e. an increase on aggregate risk. Our results strongly favour the second hypothesis. “Macro fundamentals” like devaluation risk, the EMBI spread, the change in international reserves and the change in industrial production, played an important roll in explaining the behavior of deposits during the crisis. On the contrary , banks’ “fundamentals” did not help to explain the dynamics of deposits in this crisis, with the exception of a leverage ratio. We also introduced the interest by individual banks on deposits, to test if depositors took it as an indicator of banks’ strength, flying more intensely from banks that paid higher interest rates to retain deposits. The results for the complete sample period confirm this intuition. The share of government debt holdings in banks’ portfolio was also significant for one of the sub periods of the sample, confirming that banks that were large lenders of the government were subject to a more intense run.